(3RjGOGJ GdKbGJ (B:s (3OQGSI JWHjbjI ef UMjM eSde (B/s - (3GdZRGhj, EHQGgje eMeOs; (3GdEeGe eSde, eSde Hf GdMLGL Hf eSde,s 204-261 (3g`(B.s ((3GdbGgQI (B:s (3OGQ GdBaGb ddfTQ hGdJhRjY,s, 2010)
(3GdeJhf GdMOjKjI(B-(3GdUMGM(B-(3UMjM eSde(B.s
Keywords: (3GdMOjKs -- (3ESfGO UMjMs; (3GdMOjKs -- (3UMjM eSdes